2001
DOI: 10.1161/01.cir.104.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Serum Carboxy-Terminal Propeptide of Procollagen Type I in Assessment of the Cardioreparative Ability of Antihypertensive Treatment in Hypertensive Patients

Abstract: These findings suggest that the ability of antihypertensive treatment to regress fibrosis in hypertensives with biopsy-proven myocardial fibrosis is independent of its antihypertensive efficacy. Our data also suggest that blockade of the angiotensin II type 1 receptor is associated with inhibition of collagen type I synthesis and regression of myocardial fibrosis in hypertensives. Thus, determination of serum PIP may be useful to assess the cardioreparative properties of antihypertensive treatment in hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
2
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(178 citation statements)
references
References 25 publications
10
159
2
7
Order By: Relevance
“…36 In accordance with this observation, angiotensin II receptor blockade has been shown to significantly reduce multiple markers of inflammation (C-reactive protein, TNF-a, IL-6 and monocyte chemotactic protein-1) in hypertensive patients. 37 Haemodynamic changes in atria. The excessive increase in afterload imposed by hypertension will lead to cardiac compensation with progressive thickening of the LV wall and consequent LVH.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…36 In accordance with this observation, angiotensin II receptor blockade has been shown to significantly reduce multiple markers of inflammation (C-reactive protein, TNF-a, IL-6 and monocyte chemotactic protein-1) in hypertensive patients. 37 Haemodynamic changes in atria. The excessive increase in afterload imposed by hypertension will lead to cardiac compensation with progressive thickening of the LV wall and consequent LVH.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…It has been proposed that the excess of myocardial collagen seen in hypertension is the result of both increased collagen synthesis and decreased collagen degradation. 2 Recent experimental 3,4 and clinical 5 findings suggest that the interaction of angiotensin II with its type 1 (AT 1 ) receptors plays a critical role in alterations of collagen type I metabolism and development of myocardial fibrosis in arterial hypertension.…”
mentioning
confidence: 99%
“…Pharmacological anti-hypertensive interventions within 1 year clarified the significant difference in effects on surrogate markers observed in previous clinical studies. [38][39][40] If the number of study subjects was much more in this study, we might have observed a clear difference in the effects on markers between the two regimens. However, the desirable endpoints of clinical trials are cardiovascular and cerebrovascular events and death, and hence future clinical studies with more patients and longer observational period are required.…”
Section: Limitationsmentioning
confidence: 87%